Antibiotic susceptibility of Gram-negatives isolated from bacteremia in children with cancer. Implications for empirical therapy of febrile neutropenia. (March 2015) - Castagnola, Elio; Caviglia, Ilaria; Pescetto, Luisa; Bagnasco, Francesca; Haupt, Riccardo; Bandettini, Roberto
ABSTRACT : Background: Monotherapy is recommended as the first choice for initial empirical therapy of febrile neutropenia, but local epidemiological and antibiotic susceptibility data are now considered pivotal to design a correct management strategy.Aim: To evaluate the proportion of Gram-negative rods isolated in bloodstream infections in children with cancer resistant to antibiotics recommended for this indication.Materials & methods: The in vitro susceptibility to ceftazidime, piperacillin-tazobactam, meropenem and amikacin of Gram-negatives isolated in bacteremic episodes in children with cancer followed at the Istituto "Giannina Gaslini", Genoa, Italy in the period of 2001–2013 was retrospectively analyzed using the definitions recommended by EUCAST in 2014. Data were analyzed for any single drug and to the combination of amikacin with each β-lactam. The combination was considered effective in absence of concomitant resistance to both drugs, and not evaluated by means of in vitro analysis of antibiotic combinations (e.g., checkerboard).Results: A total of 263 strains were evaluated: 27% were resistant to piperacillin-tazobactam, 23% to ceftazidime, 12% to meropenem and 13% to amikacin. Concomitant resistance to β-lactam and amikacin was detected in 6% of strains for piperacillin-tazobactam, 5% for ceftazidime and 5% for meropenem. During the study period there was a nonsignificant increase in the proportions of strains resistant to β-lactams indicated for monotherapy, and also increase in the resistance to combined therapies.Conclusion: in an era of increasing resistance to antibiotics guideline-recommended monotherapy could be not appropriate for initial empirical therapy of febrile neutropenia. Strict local survey on etiology and antibiotic susceptibility is mandatory for a correct management of this complication in cancer patients.